Kinetic bottlenecks to chemical exchange rates for deep-sea animals - Part 2: Carbon Dioxide - Hofmann, Andreas F.; Peltzer, Edward T.; Brewer, Peter G. (Biogeosciences, 2013)
Increased ocean acidification from fossil fuel CO2 invasion, from temperature-driven changes in respiration, and from possible leakage from sub-seabed geologic CO2 disposal has aroused concern over the impacts of elevated CO2 concentrations on marine life. Discussion of these impacts has so far focused only on changes in the oceanic bulk fluid properties (Delta pH, Delta [Sum CO2], etc.) as the critical variable and with a major focus on carbonate shell formation. Here we describe the rate problem for animals that must export CO2 at about the same rate at which O2 is consumed. We analyse the basic properties controlling CO2 export within the diffusive boundary layer around marine animals in an ocean changing in temperature (T) and CO2 concentration in order to compare the challenges posed by O2 uptake under stress with the equivalent problem of CO2 expulsion. The problem is more complex than that for a nonreactive gas, since with CO2 the influence of the seawater carbonate acid-base system needs to be considered. These reactions significantly facilitate CO2 efflux compared to O2 intake at equal temperature, pressure and fluid flow rate under typical oceanic concentrations. The effect of these reactions can be described by an enhancement factor, similar to that widely used for CO2 invasion at the sea surface. While organisms do need to actively regulate flow over their surface to thin the boundary layer to take up enough O2, this seems to be not necessary to facilitate CO2 efflux. Instead, the main impacts of rising oceanic CO2 will most likely be those associated with classical ocean acidification science. Regionally, as with O2, the combination of T ,P and pH/pCO2 creates a zone of maximum CO2 stress at around 1000m depth.